A comparative study of mode I delamination behavior of unidirectional glass fiber-reinforced polymers with epoxy and polyurethane matrices using two methods. (1st February 2019) - Montenegro, D.M.; Pappas, G.; Botsis, J.; Zogg, M.; Wegener, K.
Highlights: Polyurethane/glass fiber composite is 4 times tougher than epoxy/glass composite. Cohesive interface failure leads to higher toughness and fiber bridging. Direct and Indirect methods are used to identify traction-separation relations. The indirect method gives better predictions of load-displacement and R-curves. Abstract: The mode I delamination behavior of a unidirectional glass-fiber reinforced polymer with a prototype elasto-plastic polyurethane matrix (GF/PU) was investigated and compared with that of glass/epoxy (GF/EP) using double cantilever beam specimens. Fracture resistance was assessed using experimental data based on the strain energy release rate (ERR), G, calculated by means of the modified compliance calibration, and the J -integral, calculated using the applied force and arm rotations measured by digital image correlation. The fracture energies given by the two methods differed by ∼5%. In both systems large scale bridging was observed and fracture resistance at initiation and steady state was about 4 times greater in GF/PU and correlated to adhesive failure in GF/EP and cohesive in GF/PU. Since the fiber sizing was the same, the higher ERR of GF/PU was attributed to strong glass/PU interface allowing higher local matrix strains and larger fiber bundles to develop. Traction-separation relations were determined by the direct and an indirect method using Fiber Bragg Grating sensors to construct numerical models to simulate the delamination process. The simulated force-displacement and R -curve data were in good agreement with experiments.